Ethyl alcohol: experimental agent for interventional therapy of neurovascular lesions. - Pevsner, P H; Klara, P; Doppman, J; George, E; Girton, M (American Journal of Neuroradiology, 1983)
Perfusion of absolute ethyl alcohol into the middle cerebral artery of six rhesus monkeys was performed using the Pevsner miniballoon catheter system. The animals were sacrificed by thoracotomy and intracardiac perfusion of a mixed aldehyde solution for fixation. Preliminary angiography and electron microscopy suggest absolute ethyl alcohol is a good neurovascular occlusive agent, and a possible replacement for isobutyl 2-cyanoacrylate in the treatment of angiomas and tumors.